Prevalence of candidemia and associated candida subtypes following severe sepsis in non-neutropenic critically ill patients - Kashiha, Arefeh; Setayesh, Neda; Panahi, Yunes; Ahmadi, Arezoo; Soltany-Rezaee-Rad, Mohammad; Najafi, Atabak; Rouini, Mohammad Reza; Namipashaki, Atefeh; Sahebkar, Amirhossein; Mojtahedzadeh, Mojtaba (Acta Biomedica Atenei Parmensis, 2018)
Background: Invasive candidiasis management through the rapid initiation of appropriate antifungal therapy has been shown to be associated with the better prognosis, improved clinical outcome and reduced mortality in critically ill patients. Therefore, selection of  an appropriate antifungal therapy should be based on the distribution of candida species and the pattern of antifungal resistance. This study aimed to assess the prevalence of candidemia and associated subtypes following severe sepsis in non-neutropenic critically ill patients. Methods: This study was a cross-sectional study that was conducted on severe sepsis patients stayed at least seven days in intensive care unit. Patients less than 18 years old, pregnant and breastfeeding patients, immunocompromised patients, neutropenic patients, patients with concurrent use of antifungal medicines and cytotoxic agents were excluded.To asses the candidemia, one mililiter of patients’ blood sample was collected. Sample analysis was performed by Real-Time PCR and high resolution melting curve analysis method. Results: Thirty-one critically ill patients were recruited in this study over 12-month period. Candidemia with a detection limit of 100 pg per 0.2 ml blood sample was not recognized in any of the included patients. Conclusion: The present result indicates low incidence of candidemia in the targeted intensive care units, but other factors such as small sample size, exclusion of patients with compromised immune system and the low fungal load at the time of sampling may also account for our observation.